On the design of shell-and-tube heat exchangers under uncertain operating conditions - Caputo, Antonio C.; Federici, Alessandro; Pelagagge, Pacifico M.; Salini, Paolo (Applied thermal engineering, 2022)
•Traditional design methods for heat exchangers ignore variability and uncertainty.•Uncertainty may be of both type aleatory and epistemic.•For heat exchanger design under uncertainty five design methodology may be used.•Alternative methods may give different results and they are not exchangeable.•There isn’t a preferred method to handle uncertainty: neglecting it may be dangerous. This paper addresses the problem of designing shell and tube heat exchangers operating under uncertain conditions. Traditional design methods assume constant process conditions and known value of thermal design factors. Thus may fail to meet specifications when operational conditions change. Use of safety factors or worst-case design often leads to conservative design and equipment oversizing. No guideline is available in the literature for choosing a design approach. In order to provide designers better awareness on this issue, we investigate when uncertainty should be taken into account, what are the advantages and drawbacks of available approaches for design under uncertainty, and which is the preferred method to be applied in specific problem instances. To answer the above research questions, comparative sizing of equipment is carried out under consistent assumptions adopting five alternative design methods; namely design for nominal reference condition with verification of off-design performances, worst case design, use of safety margins, design to optimize a prescribed objective function, and robust design. Either random uncertainty in external process conditions, and epistemic uncertainty in heat transfer coefficients and fouling resistances are considered. Different types of specifications (more/less is better or nominal is better) are accounted for. Probability of meeting specifications and resulting geometrical characteristics are compared. It is the first time that a similar comparison is carried out, and results discussion allows to identify merits and limitations of the considered approaches. It is found that no single approach is superior, as any method can be suited to a design situation but perform poorly in other cases. Justification for explaining the observed behaviour is used in order to provide guidance to designers in choosing the preferable design method for a specific instance resulting in more cost-effective equipment configuration with higher probability of meeting specifications.